(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the adoption of new information and communication technologies a educational process of higher school and new approaches of ICT using in teaching. The results of labour techers survey different age-old groups in urban and rural schools as for the competence in information and communication technologies sphere are generalized the reasons of low level development of the investigated phenomenon are analyzed.